Navigating a Masculine Domain: Gender, Work, and Inequalities in India’s Food Delivery Platforms - Koolanneri, Mohammed Anfas; Augustian, Sandra Maria (Sociološki pregled, 2026)
In the growing discourse about work in the gig economy, the experience of women gig workers remains underexplored. The intersection of peculiar work organisation in gig platforms and existing gendered social norms produces variegated outcomes across different contexts. This study examines how women food delivery workers enter, sustain, and navigate India’s food delivery platforms, a sector largely perceived as a ‘masculine’ domain. Employing a qualitative research design, this study draws on 20 semi-structured interviews with women and men food delivery workers from major food delivery platforms operating in Thiruvananthapuram, India. The findings revealed how gendered social norms are reflected and reproduced in the policies and practices of food delivery platforms. These dynamics restrict women’s participation, shape their working hours, and ultimately widen the earning gap between men and women in food delivery platforms. This study underscores the need for policies and practices that promote positive discrimination to enhance women’s workforce participation and ensure equitable earnings, and foster dignified and inclusive working conditions within the gig economy.
Keywords: food delivery platforms; gender and work; gig economy; India; women gig workers